Cabergoline-induced tricuspid regurgitation: Case report and review of literature - Mohammad Hayat Bhat; Syed Mushtaq; Sameena Saba; Riyaz Saif; Gazanfar Ali (Indian Journal of Endocrinology and Metabolism, 2011)
The increased risk of cardiac valve disease in patients treated for Parkinson′s disease with cabergoline has raised concerns about the safety of treatment with ergot-derived dopamine agonists in patients with endocrine diseases, especially prolactinoma. Concern is raised because the use of cabergoline was associated in one study with an increased prevalence of moderate tricuspid regurgitation, and in two other studies with mild tricuspid regurgitation. Furthermore, the use of cabergoline was associated with increased frequencies of valvular thickening, calcifications, and increased mitral tenting area.